2015
DOI: 10.1016/j.jhevol.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

On the evidence for human use and control of fire at Schöningen

Abstract: When and how humans began to control fire has been a central debate in Paleolithic archaeology for decades. Fire plays an important role in technology, social organization, subsistence, and manipulation of the environment and is widely seen as a necessary adaptation for the colonization of northern latitudes. Many researchers view purported hearths, burnt wooden implements, and heated flints from Schöningen as providing the best evidence for the control of fire in the Lower Paleolithic of Northern Europe. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 117 publications
(191 reference statements)
0
33
0
Order By: Relevance
“…Allen and Macphail 1987;) have advocated their combined use in archaeological sites of varied age to study ancient agriculture, weathering processes and human use of fire (e.g. Ajas et al 2013;Dockrill and Simpson 1994;Marmet et al 1999;Stahlschmidt et al 2015;Tsatskin and Nadel 2003;Tsatskin and Zaidner 2014). Magnetic susceptibility provides information about minerals that are difficult to identify using basic optical properties in thin section.…”
Section: Integrated Approaches To the Study Of Sedimentation In Rocksmentioning
confidence: 99%
“…Allen and Macphail 1987;) have advocated their combined use in archaeological sites of varied age to study ancient agriculture, weathering processes and human use of fire (e.g. Ajas et al 2013;Dockrill and Simpson 1994;Marmet et al 1999;Stahlschmidt et al 2015;Tsatskin and Nadel 2003;Tsatskin and Zaidner 2014). Magnetic susceptibility provides information about minerals that are difficult to identify using basic optical properties in thin section.…”
Section: Integrated Approaches To the Study Of Sedimentation In Rocksmentioning
confidence: 99%
“…Moreover, there are numerous examples in Paleolithic archaeology where features that superficially resembled hearths turned out to be something unrelated to fire Goldberg et al 2001;Weiner et al 1998)-manganese in the case of Fontéchevade (Chase 2009), diagenesis in the case of Zhoukoudian layers 4 and 10 (Goldberg et al 2001;Weiner et al 1998), and organic residues in the case of Schöningen (Stahlschmidt et al 2015). At La Cotte de St. Brelade, Callow et al (1986), reported that B[p]ossible hearths were initially noted in all layers … [b]ut detailed analysis indicates that not one of these can be confirmed as a true hearth in situ.…”
Section: How Well Does the Evidence Hold Up At Other Sites?mentioning
confidence: 99%
“…Pyrotechnology is considered to be one of the most significant technological achievements in human evolution (Berna and Goldberg 2007;Brown et al 2009;Clark and Harris 1985;Courty et al 2012;de la Rúa and Diez Martín 2011;Goldberg et al 2012;Villa, Bon, and Castel 2002) although this statement is questioned by some authors based on the lack of direct evidence for human control of fire in northern latitudes (Dibble et al 2017;Sandgathe 2017;Sandgathe et al 2011aSandgathe et al , 2011bStahlschmidt et al 2015). The anthropogenic control of fire resulted in substantial changes in human subsistence, for example, providing a source of warmth and light, leading to the emergence of cooking practices (smoking, drying) and providing protection against predators (Blasco et al 2016a;Carmody and Wrangham 2009;Clark and Harris 1985;Goldberg et al 2012;Gowlett 2006;Gowlett et al 1981;James et al 1989;Preece et al 2006;Wrangham 2009;Wrangham et al 1999), as well as in socialisation and spatial organisation (Blasco et al 2016a;Henry et al 2004;Hietala 2003;Machado and Pérez 2015;Martínez-Moreno et al 2016;Sañudo, Blasco, and Fernández Peris 2016;Vallverdú et al 2010Vallverdú et al , 2012Vaquero and Pastó 2001;Vaquero, Rando, and Chacón 2004;Vidal-Matutano 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The anthropogenic control of fire resulted in substantial changes in human subsistence, for example, providing a source of warmth and light, leading to the emergence of cooking practices (smoking, drying) and providing protection against predators (Blasco et al 2016a;Carmody and Wrangham 2009;Clark and Harris 1985;Goldberg et al 2012;Gowlett 2006;Gowlett et al 1981;James et al 1989;Preece et al 2006;Wrangham 2009;Wrangham et al 1999), as well as in socialisation and spatial organisation (Blasco et al 2016a;Henry et al 2004;Hietala 2003;Machado and Pérez 2015;Martínez-Moreno et al 2016;Sañudo, Blasco, and Fernández Peris 2016;Vallverdú et al 2010Vallverdú et al , 2012Vaquero and Pastó 2001;Vaquero, Rando, and Chacón 2004;Vidal-Matutano 2017). The timing of human control of fire is one of the most widely debated topics in the field of Palaeolithic archaeology (Berna and Goldberg 2007;de Lumley 2006;Gowlett 2006;Gowlett et al 1981;James et al 1989;Karkanas et al 2007;Roebroeks and Villa 2011;Stahlschmidt et al 2015;Wrangham 2009), since such discussion is strongly related to the consideration of fire evidence as being of either natural or anthropogenic origin (Bellomo 1994;James et al 1989;Roebroeks and Villa 2011). The most common fire evidence consists of archaeological features showing traces of having been subjected to heating, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation